SAE Technical Paper Series 2015
DOI: 10.4271/2015-01-0022
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Aerodynamic Analysis of Cornering Vehicles

Abstract: When a vehicle travels through a corner it can experience a significant change in aerodynamic performance due to the curved path of its motion. The yaw angle of the flow will vary along its length and the relative velocity of the flow will increase with distance from the central axis of its rotation. Aerodynamic analysis of vehicles in the cornering condition is an important design parameter, particularly in motorsport. Most racing-cars are designed to produce downforce that will compromise straight-line speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Thus, it was aligned to the tangent of the body's path whilst the side-force, by definition, as the force acting orthogonally to the drag force; as illustrated in Figure 11. This follows Keogh et al [20] and Keogh [22], that the drag force is linearly proportional to the moment acting about the GCoR (M DWi ) to oppose the circular path of the body. The lift force vector is unaltered.…”
Section: Post-processingsupporting
confidence: 54%
See 1 more Smart Citation
“…Thus, it was aligned to the tangent of the body's path whilst the side-force, by definition, as the force acting orthogonally to the drag force; as illustrated in Figure 11. This follows Keogh et al [20] and Keogh [22], that the drag force is linearly proportional to the moment acting about the GCoR (M DWi ) to oppose the circular path of the body. The lift force vector is unaltered.…”
Section: Post-processingsupporting
confidence: 54%
“…The cornering condition requires the consideration of both the topology of the computational domain and the simulation of motion. Regarding the topology, either a rectangular computational domain or a curved domain must be selected with the associated boundary conditions, as discussed in [20]. Whilst it is easier to apply the appropriate boundary conditions with a curved domain, it does not allow the simulation of multiple corner radii via the same domain or mesh nor does it allow the simulation of multiple operating conditions such as the straight-line condition.…”
Section: Physics Modellingmentioning
confidence: 99%
“…Since the vehicles velocity vector is not constant over the entire body while cornering, the drag force calculation needs to be modified. The drag force is calculated as [4]…”
Section: Curved Drag Forcementioning
confidence: 99%
“…Fuel consumption is measured with standardized driving cycles such as Worldwide harmonized Light vehicles Test Procedures (WLTP) [2]. The WLTP cycle only considers flows in the driving direction of the vehicle, however, studies in simplified geometries have shown that aerodynamic properties can be a ected by cornering [3], [4]. Keogh [3], for instance, studied the impact of cornering on an inverted wing and found significant changes in the flow structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation